Effects of forearm wearable resistance on acceleration mechanics in collegiate track sprinters. Issue 10 (25th November 2020) - Uthoff, Aaron M.; Nagahara, Ryu; Macadam, Paul; Neville, Jono; Tinwala, Farhan; Graham, Scott P.; Cronin, John B.
Abstract: Arm action is critical for optimising sprinting performance. This study aimed to examine overground sprinting performance and step characteristics during unloaded and 2% body mass (BM) forearm wearable resistance loaded sprinting. Fourteen collegiate male track sprinters performed unloaded and forearm loaded sprints over thirty metres of in-ground force plates. Step kinematics and relative kinetics were compared between the unloaded and forearm loaded conditions over four acceleration phases (i.e. steps 1–4, 5–8, 9–12 and 13–16). Affixing 2% BM loads to the forearms did not significantly alter 0–30-m sprint times ( p  > 0.05; −1.38 to −1.75%; ES = −0.38 to −0.54). Sprinting with forearm loads resulted in significant ( p  ≤ 0.05) increases in relative propulsive impulse (5.48%; ES = 1.09) and step length (4.01%; ES = 1.04) over the 1st acceleration phase. Relative vertical impulse was the only variable to change over the middle two acceleration phases (3.94–4.18%; ES = 0.77–1.00). Over the last acceleration phase stride frequency was lower (−4.86%, ES = −0.92), yet both flight time (7.70%; ES = 0.79) and vertical impulse (4.12%; ES = 0.89) increased. These findings provide interesting programming implications for coaches who wish to improve the determinants of sprinting via dedicated and specific arm loaded training. Sprinting with forearm loads may be used to develop longer stride lengths by generating greater horizontal propulsion during early acceleration and promote alterations to step frequency and flight time imposed through greater vertical loading demands over the later phases of accelerated sprinting.